Activation of Phosphatidylcholine-Specific Phospholipase C in Breast and Ovarian Cancer: Impact on MRS-Detected Choline Metabolic Profile and Perspectives for Targeted Therapy - Podo, Franca; Paris, Luisa; Cecchetti, Serena; Spadaro, Francesca; Abalsamo, Laura; Ramoni, Carlo; Ricci, Alessandro; Pisanu, Maria Elena; Sardanelli, Francesco; Canese, Rossella; Iorio, Egidio (Frontiers in Oncology, 2016)
Elucidation of molecular mechanisms underlying the aberrant phosphatidylcholine-cycle in cancer cells plays in favor of the use of metabolic imaging in oncology and opens the way for designing new targeted therapies. The anomalous choline metabolic profile detected in cancer by magnetic resonance spectroscopy (MRS) and spectroscopic imaging (MRSI) provides molecular signatures of tumor progression and response to therapy. The increased level of intracellular phosphocholine (PCho) typically detected in cancer cells is mainly attributed to upregulation of choline kinase, responsible for choline phosphorylation in the biosynthetic Kennedy pathway, but can also be partly produced by activation of phosphatidylcholine-specific phospholipase C (PC-PLC). This hydrolytic enzyme, known for implications in bacterial infection and in plant survival to hostile environmental conditions, is reported to be activated in mitogen- and oncogene-induced phosphatidylcholine cycles in mammalian cells, with effects on cell signaling, cell cycle regulation and cell proliferation. Recent investigations showed that PC-PLC activation could account for 20-to-50% of the intracellular PCho production in ovarian and breast cancer cells of different subtypes. Enzyme activation was associated with PC-PLC protein overexpression and subcellular redistribution in these cancer cells compared with non-tumoral counterparts. Moreover, PC-PLC co-immunoprecipitated with the human epidermal growth factor receptor-2 (HER2) and EGFR in HER2-overexpressing breast and ovarian cancer cells, while pharmacological PC-PLC inhibition resulted into long-lasting HER2 downregulation, retarded receptor re-expression on plasma membrane and anti-proliferative effects. This body of evidence points to PC-PLC as a potential target for newly designed therapies, whose effects can be pre-clinically and clinically monitored by metabolic imaging methods.